2000
DOI: 10.1081/pdt-100100527
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Myotoxicity of Pharmaceutical Buffers Using an In Vitro Muscle Model: Effect of pH, Capacity, Tonicity, and Buffer Type

Abstract: The purpose of the present study was to investigate the myotoxicity of three buffers containing carboxylic acid groups (i.e., acetate, succinate, and citrate) as a function of their pH, capacity, and tonicity. The myotoxicity of these buffers in the range of pH 2-6 and 0.001-0.1 M buffer capacity was assessed using cumulative creatine kinase (CK) release from an isolated rodent muscle model following injection. Phenytoin and 0.9% NaCl injection were used as positive and negative controls, respectively. Buffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The acidic solution devitalised the tissue [15], thus favouring the propagation of anaerobic infection. Toxin production led to the development of a severe localised inflammatory reaction with marked oedema which, in some cases, was followed by a life-threatening systemic illness, characterised by hypotension, a leukaemoid reaction and necrotising fasciitis.…”
Section: Outbreak Of Severe Illness Among Injecting Drug Users 975mentioning
confidence: 99%
“…The acidic solution devitalised the tissue [15], thus favouring the propagation of anaerobic infection. Toxin production led to the development of a severe localised inflammatory reaction with marked oedema which, in some cases, was followed by a life-threatening systemic illness, characterised by hypotension, a leukaemoid reaction and necrotising fasciitis.…”
Section: Outbreak Of Severe Illness Among Injecting Drug Users 975mentioning
confidence: 99%
“…It is reported that citrate buffer can induce myotoxicity, which might cause local irritation after administration. [8] To reduce this possibility, lactate buffer may be more suitable. Furthermore, the inclusion of YM466 with CDs may reduce local irritation.…”
Section: Effect Of Cyclodextrins On the Solubility Of Ym466 In Aqueoumentioning
confidence: 99%
“…An ideal formulation for IV administration should contain only water and water-soluble components (salts, buffers). The acceptable range of pH for the IV formulation may be expanded with the use of a lower dosing volume but must be balanced with the in vivo tolerability requirements [47]. The acceptable pH range for IV formulations may vary from 2 to 12 [44].…”
Section: Formulationsmentioning
confidence: 99%